A study of pedestal and landscape improvement for universal design: A case study of educational area surrounding government center, Khon Kaen province - Tongpong, Nitiwadee; Santiwes, Sanchai; Nongharnpitak, Teeraphat; Prachayakupt, Pakasawan; Akkaudom, Poovares; Phuttitamakul, Warut; Tangyoo, Butsabamintra; Nanthaphorm, Anusit (Journal of Building Energy & Environment, 2021)
A study of pedestal and landscape improvement for universal design: A case study of educational area surrounding government center, Khon Kaen province. By conducting site surveys combined with current area problems and accessibility factors, the guideline for passageways environmental design and Universal Design facilities is created. The study found that the footpath is obstructed, unorganized, unsafe, and especially lack of maintenance. This study presents the concept of key public area pedestal design improvement. It is categorized into 5 levels as follow; level 1: area improvement by organizing, level 2: area improvement by simple repairing or renovating, level 3: area improvement by renovating or moving facilities to optimize it, level 4: area improvement by demolishing and small constructing, and level 5: area improvement by demolishing and new constructing. The cooperation from government and private sectors together with all people are required for public area improvement. Thus, in order to have the genuine area improvement for Universal Design, everyone and every organization need to prioritize and understand the right, equality and pay respect to others.